Investigação de propriedades no estado sólido de triazenos simétricos 1,3-diarilsubstituídos e complexos com Co(III) e Cu(II) com o ligante 1,3-bis(4-metoxicarbonilfenil)triazenido - Westphalen, André Bilibio (2007)
In this work it was synthesized and determinate the crystalline/molecular structure of two pré ligands triazene simetric: 1,3−bis−(4−acethylamidephenyl)triazene [H3CC(O)NHC6H4NNNC6H4NH(O)CCH3] (1) e o 1,3−bis−(4−ethoxicarbonylphenyl)triazene [H5C2OC(O)C6H4NNNC6H4C(O)OC2H5] (2), one Cu(II) complex (3) and one Co(III) complex (4), being that the two complexes involve the ligand 1,3-bis(4- methoxicarbonylphenyl)triazenide ligands previously deprotonated. Also it was presented the synthesis of pré ligand. The compound H3CC(O)NHC6H4NNNC6H4NH(O)CCH3] (1) crystallizes in monoclinic system, space group C2/c, with cell parameters a=16,0434(8)Å, b=13,0914(6)Å,c=13,0914(6)Å, β = 91.595(2)°, V=3207,2(3)Å 3 ; Z=8. The refinement of this structure converge to the follow discordance indexes wR1=0,0707e wR2=0,1621. The compound [H5C2OC(O)C6H4NNNC6H4C(O)OC2H5] (2) crystallizes in triclinic system, space group P(-1), with cell parameters a=7,65300(10) Å, b=13,4633(2) Å, c=18,0173(3) Å, α = 74,6550(10)°, β = 82,3950(10)° , у = 79,0350(10)°, 1748,5(14) Å 3 ; Z=4. The refinement of this structure converge to the follow discordance indexes wR1=0,1299 e wR2=0,1708. The complex {Cu[H3COC(O)C6H4NNNC6H4C(O)OCH3]2[(CH3)2N]2} (3) crystallizes in triclinic system, space group P(-1) with cell parameters a=7,91600(10)Å, b=9,1596(2)Å, c=13,4476(2)Å, α=105,4130(10)°, β=96,6370(10)°, у=96,1510(10)°, V=923,96(3)Å3; Z=2. The refinement of this structure converge to the follow discordance indexes wR1 = 0,0433, wR2 = 0,1293. The sphere of coordination of Cu(II) ion is formed by two deprotonated triazene ligands and two molecules of dimethylamine. The characteristic effect of Jahn-Teller s distortion expands the coordination geometry of Cu(II) ion to octahedral axially distorted. The complex {Co[H3COC(O)C6H4NNNC6H4C(O)OCH3]3} (4) crystallizes in triclinic system, space group C2/c, with cell parameters a=13,4346(7) Å, b=29,5701(17) Å, c=13,8951(7) Å, β= 107,274(2)°, V= 5271,0(5) Å3; Z=4. The refinement of this structure converge to the follow discordance indexes wR1=0,1081e wR2=0,2278. The structure of this complex presents three ligands triazenides double-toothed. The coordination geometry of the ion Co3+ is octaedric, being distorted and conferring a local asymmetry for the molecule, where it is converges in last analysis to geometry of distorted rombic coordination.